Chinese motifs in contemporary design. - SendPoints Publishing Co. (Guangzhou Beijing Shanghai : SendPoints, 2017)
This book presents over 700 Chinese motifs, showcasing 35 outstanding works inspired by Peking Opera, Paper Cutting, Animal Motifs and Auspicious Motifs, etc. Well-known designers were invited to share their design inspiration and experience concerning Chinese motifs to offer an insight into traditional Chinese culture. CD-ROM (1. The facial make-up in Chinese opera, 2. Chinese paper cutting, 3. New year painting, 4. The auspicious pattern, 5. The animal motif, 6. Plants and flowers motif).
Includes index
Keywords: Decoration and ornament -- Pictorial works -- Themes, motives -- China; Decoration and ornament -- Themes, motives; Operas, Chinese, in art; Paper work -- China; Bildband